2008
DOI: 10.1590/s0034-89102008005000013
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade interobservador da Classificação Internacional de Cuidados Primários

Abstract: OBJECTIVE:The International Classifi cation of Primary Care was developed as an attempt to overcome the limitations of the International Statistical Classifi cation of Diseases and Related Health Problems, 10th revision, when used for primary health care. The aim of the study was to evaluate the interobserver reliability of the International Classifi cation for Primary Care when coding reasons for health-related interruption of daily activities. METHODS:Data analyzed pertained to 801 subjects from Phase 2 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
1
5
1
3
Order By: Relevance
“…(16,17) The simple agreement average of the interobserver evaluation corresponded to 97.6%, and the mean simple agreement of the test and retest was 97%, indicating an excellent agreement, in line with other studies. (13)(14)(15)(16)(17)(18)(19) The data revealed that the instruments of the Quality Assurance program present equivalence and excellent stability when compared to those from other studies. (16)(17)(18)(19) We believe that, through these instruments, the managers of the National Transplantation System can encourage hospital managers to use these tools in order to develop indicators, based on concise information obtained from the medical records of patients deceased at Critical Patient Units.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…(16,17) The simple agreement average of the interobserver evaluation corresponded to 97.6%, and the mean simple agreement of the test and retest was 97%, indicating an excellent agreement, in line with other studies. (13)(14)(15)(16)(17)(18)(19) The data revealed that the instruments of the Quality Assurance program present equivalence and excellent stability when compared to those from other studies. (16)(17)(18)(19) We believe that, through these instruments, the managers of the National Transplantation System can encourage hospital managers to use these tools in order to develop indicators, based on concise information obtained from the medical records of patients deceased at Critical Patient Units.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the inter-observer agreement of items lies within the levels recommended by other authors, with Kappa values of 0.68, 0.73, 0.80, 0.92, 0.97. (13)(14)(15)(16)(17)(18)(19) Still, in these studies, values of 0.68, 0.86, 0.89 and 0.92 for the tests and re-tests were identified. (16,17) The simple agreement average of the interobserver evaluation corresponded to 97.6%, and the mean simple agreement of the test and retest was 97%, indicating an excellent agreement, in line with other studies.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations